Evaluation the Corrosion of Mild Steel Rings in Simulated Conditions of Natural Gas Transportation - Shneine, Jewad K (Al-Nahrain Journal of Science, 2017)
Corrosion of steel rings (steel tubes) under natural gas production conditions has been studied in a 2 L glass autoclave. Steel tubes, axially constructed with cavities of aspect ratios 3×1 mm, were exposed to CO2 saturated chloride salt solutions in a glass autoclave for 4 days at a flow rate of 6m/s and CO2 flow of 5 bar. Effect of temperature, chloride ion concentration, and inhibitor ratio has been studied. Accordingly, removal mass, surface layer mass and the corrosion rate were evaluated at different conditions. Fe2+ concentrations and pH values were also evaluated. The corrosion degree of the tested samples is assessed by polarizing microscope at different magnification values. Results showed that high corrosion rates affected by high temperatures and high chloride concentrations, have been particularly reduced by addition of Dodisclae V3962 inhibitor. Formation of a fixed surface layer mass might be the reason for the high corrosion inhibition. [DOI: 10.22401/JUNS.20.3.08]